Motivación y desempeño laboral en profesionales de enfermería durante la pandemia por covid-19. Hospital Santa Gema Yurimaguas 2022 - Jarama Torres, Ana Leticia (2023)
The study aims to determine the relationship that exists between motivation and work performance in Nursing Professionals during the COVID-19 pandemic. Hospital Santa Gema-Yurimaguas 2022. The study had a quantitative, descriptive, correlational approach, with a non-experimental, and cross-sectional design; The sample is made up of 50 Nursing professionals. The technique used was the survey, the instruments used were the questionnaire on motivational factors (reliability 0.835) and work performance (reliability 0.820). Having as results; that work motivation is at a level that is moderately adequate in 52% and adequate in 48%, likewise, the level of extrinsic motivation is moderately adequate in 44% and adequate in 56% and work performance at a regular level in 72%. % and good in 28%, It is concluded that there is a significant relationship between motivation and work performance, given that the significance was 0.001 and the correlation coefficient equal to 0.462, therefore it is concluded that motivation is a determining factor in the work performance of nursing professionals at the Santa Gema de Yurimaguas Hospital.